Mismatch between Anthropometry Characteristics of Nigerian Occupational Bus Drivers and the In-Vehicle Measurement - Fajobi Moses O., Onawumi Ayodele S.1., Mfon Udoh M. O. & Awoyemi Elijah A. (Covenant Journal of Engineering Technology, 2019)
The characterization of interfacing elements of in-vehicle and driver’s anthropometric variables of a randomly selected operators with sample size of 161 subjects of commercial buses in the study area were considered in this work. Participatory ergonomic intervention approach was employed in data mining, opinion gathering and subsequent analysis. Related variables between the two systems were compared to establish fitness as well as the level to which human operator were accommodated in the vehicle dimension. A few cases of misfit were recorded based on drivers’ opinion and the measurements taken. Work related musculoskeletal disorder experienced by the users under study were traceable to inappropriate design variable of the in-vehicle elements.